Strengthening Human Resource Capacity and Capability in the Public Sector in the Digital Era: English - Albert Antonio; Asropi (Social Science Academic, 2026)
Digital transformation has become a strategic agenda for public sector organizations to improve governance, service quality, and organizational performance. However, technological advancement alone is insufficient to ensure successful digital transformation, as it also requires competent human resources, adaptive leadership, and sustainable employee well-being. Therefore, this study aims to analyze strategies for strengthening public sector human resource capacity and capability by integrating digital upskilling, transformational leadership, and employee well-being within a comprehensive conceptual framework. This study employed a qualitative approach using a literature review method by synthesizing evidence from recent peer-reviewed journal articles, international reports, and relevant policy documents. The findings indicate that digital upskilling enhances civil servants' competencies in digital literacy, artificial intelligence, cybersecurity, data analytics, and evidence-based decision-making. Nevertheless, these competencies can only generate sustainable organizational outcomes when supported by transformational leadership that fosters innovation, continuous learning, and organizational adaptability, alongside employee well-being initiatives that mitigate technostress and maintain workforce engagement. This study concludes by proposing an integrative model that positions digital upskilling, transformational leadership, and employee well-being as complementary strategic capabilities for achieving adaptive, human-centered, and sustainable digital transformation in the public sector.